Desain Kebaya Sunda Abad Ke-20 Studi Kasus di Bandung Tahun 1910-1980 - Irma Russanti (Journal of Visual Art and Design, 2007)
The female traditional outfits of Sunda are varied according to geography, history, social life, economy, and cultural transformations that have taken place for centuries. The similarity in both cultures and historical background had resulted in the similarity on structural design of the various female outfits in this area. This study focuses to identify various styles of kebaya Sunda that shared similarity of features. The word Sunda itself was used as a collective term, and apparently had a relation with the original place and culture of the kebaya wearers "“ female Sundanese. Given wide geographical area and historical richness of Sunda, the study focuses on the area of Bandung during the period of 1910"“1980. The study employed a descriptive analysis that was based on the historical approach, in an attempt to describe the cultural transformation of kebaya as the traditional female outfit that had taken place in Sunda area. To identify design features of kebaya Sunda, the study employed both synchronic and diachronic approaches. To analyze the effect of modernization toward aesthetical shift and changes of design in kebaya Sunda during 1910-1980, the study employed aesthetical approach. In addition, the study also looks into the influence of social stratification upon the classification of the designs in kebaya Sunda. Results suggest that: (1) Design features of the kebaya Sunda had accumulated into five different styles (V neckline, wide samleh, small samleh, cowak, and triangle bef), (2) The modern education and the changes of thinking pattern, trend mode and textile, and the technological development of pattern making had greatly influenced the aesthetical shift of the kebaya Sunda design, thus greatly affecting their design changes (sleeve shape, collars, necklines, proportions, textures, silhouettes, constructions, and decoration varieties, (3) The influence of the social stratification to the design classification of kebaya Sunda in Bandung in 1941 was evident, when kebaya menak and kebaya cacah were created. Their significant differences appear in shapes, lines, silhouettes, proportions, textures, decoration varieties, details, and trimmings. The style of kebaya menak was predominantly used by all styles of the kebaya Sunda whereas kebaya cacah tended to use small samleh style.